Etnobotani Tumbuhan Liar sebagai Sumber Pangan di Dusun Mendiro, Kecamatan Wonosalam, Jombang - Lailatus Sholichah; Dinar Alfidhdhoh (Jurnal Ilmu Pertanian Indonesia, 2020)
Mendiro Village is a small hamlet located in Wonosalam District, Jombang Regency. Indigenous villagers in Mendiro Village have a knowledge related to the use of wild plants as foods to fullfill life necessities. This study aims to determine the types, parts of plant organs, processing methods, and categories of utilization of wild plants in Mendiro Village, Wonosalam District, Jombang Regency. This research was conducted in March-May 2018. This study used a qualitative method with ethnobotany approach techniques through semistructured interviews and participatory observation. The results of the study found 43 species of wild plants that were used as food plants and belonging to the 26 families. The most widely used families were Asteraceae, Lamiaceae, and Poaceae. Plant parts that were widely used were leaves and fruits. The utilization of wild plants is conducted by directly consuming and by processing first. Wild plants are found in several places, such as forests, fields, yards, and on the roadside. The highest frequency of citation in this study that reached 100% are for pegagan (Centella asiatica), jelateng (Toxicodendron radicans), basil (Ocymum basilicum), simbukan (Paederia foetida), bayam banci (Amaranthus tricolor), mint leaves (Mentha piperita Linn), mbotem (Colocasia esculenta), suweg (Morphophallus campanulatus), and kenikir (Cosmos caudatus Kunth). Keywords: citation frequency, ethnobotany, food plants, mendiro